Systemacity of descriptive geometry as the basis of its fundamental nature - Ткач, Дмитро Іванович (Pedagogy of Higher and Secondary Education, 2019)
Tkach D. І. Systemacity of descriptive geometry as the basis of its fundamental nature. The article is devoted to the proof of the fundamental nature of the discipline «Descriptive Geometry», which is taught in all technical and creative universities as a general subject. This proof is based on the dialectical unity of descriptive geometry, which is considered as an applied science and fundamental Euclidean geometry, which is descriptive geometry «represents» or models graphically.